Precursor for positive electrode active material of lithium secondary battery and method for producing positive electrode active material of lithium secondary battery
Patent Information
- Application Number
- JP2021170550
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-10-18
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2040-06-29
AI Technical Summary
【0010】 本発明によれば、電池膨れを抑制し、従来の電池よりもより長寿命の電池を製造できるリチウム二次電池正極活物質用前駆体、およびリチウム二次電池正極活物質の製造方法を提供することができる。
Smart Images

Figure 0007627820000003 
Figure 0007627820000004 
Figure 0007627820000005
Abstract
Description
[Technical Field]
[0001] The present invention relates to a precursor for a positive electrode active material for a lithium secondary battery and a method for producing a positive electrode active material for a lithium secondary battery. [Background technology]
[0002] The precursor for the positive electrode active material of a lithium secondary battery is a raw material for the positive electrode active material used in a lithium secondary battery. One example of a method for producing a positive electrode active material for a lithium secondary battery is to produce a precursor containing a metal element other than lithium, such as nickel, cobalt, manganese, or aluminum, and then mix and bake the resulting precursor with a lithium compound.
[0003] Lithium secondary batteries are already being put to practical use not only as small power sources for mobile phones and notebook computers, but also as medium- and large-sized power sources for automobiles and power storage.
[0004] In order to improve the battery characteristics of lithium secondary batteries, methods for controlling the particle size distribution of positive electrode active materials for lithium secondary batteries have been investigated. For example, it is known that the use of a positive electrode active material composed of particles with a narrow particle size distribution can provide lithium secondary batteries with excellent battery characteristics such as cycle characteristics.
[0005] As an example of such technology, Patent Document 1 describes a positive electrode active material for non-aqueous electrolyte secondary batteries in which [(d90-d10) / average particle size], an index showing the breadth of particle size distribution, is 0.60 or less. Patent Document 1 also describes that a secondary battery using such a positive electrode active material for non-aqueous electrolyte secondary batteries has high capacity, high thermal safety, and high output. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Japanese Patent Application Laid-Open No. 2015-43335 Summary of the Invention [Problem to be solved by the invention]
[0007] However, when the positive electrode active material of a lithium secondary battery comes into contact with an electrolyte, the electrolyte may decompose and generate gas. The generated gas can cause the battery to swell, shortening its lifespan. To suppress battery swelling and produce batteries with longer lifespans than conventional batteries, there was room for improvement in the positive electrode active material of a lithium secondary battery and its precursors, which are its raw materials.
[0008] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a precursor for a positive electrode active material for a lithium secondary battery, which can suppress battery swelling and enable the production of a battery with a longer life, and a method for producing a positive electrode active material for a lithium secondary battery. [Means for solving the problem]
[0009] The present invention encompasses the following [1] to [4]. [1] A precursor for a positive electrode active material of a lithium secondary battery containing at least nickel atoms, wherein the particle diameter (μm) at which the cumulative volume ratio from the small particle side is 10% in a volume-based cumulative particle size distribution curve obtained by laser diffraction particle size distribution measurement is defined as D 10 , the particle diameter (μm) at 30% is D 30 , the particle diameter (μm) at 50% is D 50 , the particle diameter (μm) at 70% is D 70 , 90% particle diameter (μm) is D 90 When the above D 10 , the D 30 , the D 50 , the D 70 , and the D 90 A precursor for a positive electrode active material of a lithium secondary battery, which satisfies the following requirements (1) to (3): (1)(D 50 -D 10 ) / D 30 ≦0.6 (2)(D 90 -D 50 ) / D70 ≦0.6 (3) 0.90≦[(D 50 -D 10 ) / D 30 ] / [(D 90 -D 50 ) / D 70 ]≦1.10 [2] The precursor for a positive electrode active material of a lithium secondary battery according to [1], represented by the following composition formula (A): Ni 1-x-y Co x M y O z (OH) 2-α ...Composition formula (A) (In composition formula (A), 0≦x≦0.45, 0≦y≦0.45, 0≦z≦3, and −0.5≦α≦2, and M is one or more metallic elements selected from the group consisting of Mg, Ca, Sr, Ba, Zn, B, Al, Mn, Ga, Ti, Zr, Ge, Fe, Cu, Cr, V, W, Mo, Sc, Y, Nb, La, Ta, Tc, Ru, Rh, Pd, Ag, Cd, In, and Sn.) [3] D above 50 The precursor for a positive electrode active material of a lithium secondary battery according to [1] or [2], wherein the value of is less than 10 μm. [4] A method for producing a positive electrode active material for a lithium secondary battery, comprising the steps of mixing the precursor for a positive electrode active material for a lithium secondary battery according to any one of [1] to [3] with a lithium compound, and firing the resulting mixture. [Effects of the Invention]
[0010] According to the present invention, it is possible to provide a precursor for a positive electrode active material of a lithium secondary battery, which can suppress battery swelling and produce a battery with a longer life than conventional batteries, and a method for producing a positive electrode active material of a lithium secondary battery. [Brief explanation of the drawings]
[0011] [Figure 1A] FIG. 1 is a schematic diagram illustrating an example of a lithium secondary battery. [Figure 1B] FIG. 1 is a schematic diagram illustrating an example of a lithium secondary battery. [Figure 2A]FIG. 2 is a schematic diagram illustrating the state inside the electrode of a positive electrode active material for a lithium secondary battery produced using the precursor of the present invention. [Figure 2B] FIG. 2 is a schematic diagram illustrating the state inside an electrode of a positive electrode active material for a lithium secondary battery produced using a precursor other than that of the present invention. [Figure 3] FIG. 1 is a schematic diagram of a liquid cyclone classifier. [Figure 4] FIG. 4 is a schematic diagram showing a laminate included in an all-solid-state lithium-ion secondary battery. [Figure 5] FIG. 5 is a schematic diagram showing the overall configuration of an all-solid-state lithium-ion secondary battery. DETAILED DESCRIPTION OF THE INVENTION
[0012] <Precursor for positive electrode active material of lithium secondary batteries> This embodiment is a precursor for a positive electrode active material for a lithium secondary battery that contains at least nickel atoms. Hereinafter, the "precursor for a positive electrode active material for a lithium secondary battery" may be referred to as a "precursor," and the "positive electrode active material for a lithium secondary battery" may be referred to as a "positive electrode active material." The precursor of this embodiment can be mixed with a lithium compound and fired to produce a positive electrode active material for a lithium secondary battery.
[0013] In one aspect of this embodiment, the precursor is composed of primary particles and secondary particles that are aggregates of the primary particles. In one aspect of this embodiment, the precursor is a powder.
[0014] The precursor of this embodiment is a particle diameter (μm) at which the cumulative volume ratio from the small particle side is 10% in a volume-based cumulative particle size distribution curve obtained by laser diffraction particle size distribution measurement. 10 , the particle diameter (μm) at 30% is D 30 , the particle diameter (μm) at 50% is D 50 , the particle diameter (μm) at 70% is D 70 , 90% particle diameter (μm) is D 90 When the above D 10 , the D30 , the D 50 , the D 70 , and the D 90 However, the following requirements (1) to (3) are met. (1)(D 50 -D 10 ) / D 30 ≦0.6 (2)(D 90 -D 50 ) / D 70 ≦0.6 (3) 0.90≦[(D 50 -D 10 ) / D 30 ] / [(D 90 -D 50 ) / D 70 ]≦1.10
[0015] The cumulative volume particle size distribution of the precursor is measured by laser diffraction scattering. For example, a dispersant is first added to the dispersion medium, and the powdered precursor is then added and stirred to obtain a precursor dispersion. The particle size distribution is then measured using a laser diffraction particle size distribution analyzer to obtain a volume-based cumulative particle size distribution curve.
[0016] The dispersion medium may be, for example, ion-exchanged water, and the dispersant may be, for example, a 20% by mass aqueous solution of sodium hexametaphosphate. As the laser diffraction particle size distribution measuring device, for example, LA950 manufactured by Horiba Ltd. can be used. It is preferable to add the powdered precursor in such a manner that the transmittance during measurement is 85±3%.
[0017] In the volume-based cumulative particle size distribution curve obtained by the above method, the particle diameter (μm) at which the cumulative volume ratio from the small particle side becomes 10% is defined as D 10 , the particle diameter (μm) at 30% is D 30 , the particle diameter (μm) at 50% is D 50 , the particle diameter (μm) at 70% is D 70 , 90% particle diameter (μm) is D 90In this specification, the term "particle size" refers to the secondary particle size.
[0018] In this embodiment, D 10 , D 30 , and D 50 satisfies the following requirement (1). (1)(D 50 -D 10 ) / D 30 ≦0.6 D 10 , D 30 , and D 50 If requirement (1) is satisfied, the particle diameter contained in the precursor is D 50 This means that the variation in particle diameter among a plurality of particles smaller than 1 / 2 mm is small.
[0019] (D 50 -D 10 ) / D 30 The value of is preferably 0.55 or less, more preferably 0.5 or less, and even more preferably 0.48 or less. (D 50 -D 10 ) / D 30 The lower limit of the value is, for example, 0.1 or more, 0.2 or more, or 0.3 or more. (D 50 -D 10 ) / D 30 The upper and lower limits of the value can be combined arbitrarily. Examples of combinations include (D 50 -D 10 ) / D 30 However, examples include 0.1 to 0.55, 0.2 to 0.5, and 0.3 to 0.48.
[0020] In this embodiment, D 50 , D 70 , and D 90 satisfies the following requirement (2). (2)(D 90 -D 50 ) / D 70 ≦0.6 D 50 , D 70 , and D90 If requirement (2) is satisfied, the particle diameter contained in the precursor is D 50 This means that, among a plurality of particles larger than 1000 nm, the variation in particle diameter among the plurality of particles is small.
[0021] (D 90 -D 50 ) / D 70 The value of is preferably 0.55 or less, more preferably 0.5 or less, and even more preferably 0.48 or less. (D 90 -D 50 ) / D 70 The lower limit of the value is, for example, 0.1 or more, 0.2 or more, or 0.3 or more. (D 90 -D 50 ) / D 70 The upper and lower limits of the value can be combined arbitrarily. Examples of combinations include (D 90 -D 50 ) / D 70 is 0.1 or more and 0.55 or less, 0.2 or more and 0.5 or less, or 0.3 or more and 0.48 or less.
[0022] A precursor that satisfies requirements (1) and (2) means that it has a particle size distribution with a narrow peak width.
[0023] The precursor of this embodiment satisfies the following requirement (3). (3) 0.90≦[(D 50 -D 10 ) / D 30 ] / [(D 90 -D 50 ) / D 70 ]≦1.10
[0024] Requirement (3) is preferably requirement (3)-1, (3)-2, or (3)-3 below. (3)-1 0.95≦[(D 50 -D 10 ) / D 30 ] / [(D 90 -D 50 ) / D 70 ]≦1.09 (3)-2 0.96≦[(D 50 -D 10 ) / D 30 ] / [(D 90 -D 50 ) / D 70 ]≦1.08 (3)-3 0.97≦[(D 50 -D 10 ) / D 30 ] / [(D 90 -D 50 ) / D 70 ]≦1.07
[0025] When a positive electrode active material for a lithium secondary battery is produced using the precursor of this embodiment that satisfies requirements (1) to (3) as a raw material, an electrode with a more uniform packing density of the positive electrode active material particles can be produced. This will be described with reference to Figures 2A and 2B. 2A is a schematic diagram illustrating the internal state of an electrode obtained from a positive electrode active material 50 produced using the precursor of this embodiment as a raw material. The amount of positive electrode active material 50 present within a given volume range is the same in region S1 and region S2. That is, the amount of positive electrode active material 50 present within a given volume within the electrode is uniform. 2B is a schematic diagram illustrating the internal state of an electrode obtained from a positive electrode active material 51 produced using a precursor other than that of the present invention. In regions S3 and S4, the amount of positive electrode active material 51 present within a given volume varies greatly. That is, the amount of positive electrode active material 50 present within a given volume within the electrode is non-uniform.
[0026] When the amount of positive electrode active material present within a given volume of the electrode is uniform, as shown in Figure 2A, the resulting electrode tends to have a uniform voltage across the electrode when the battery is charged or discharged. Such an electrode is less likely to experience high localized voltages and is less likely to generate gas due to decomposition of the electrolyte. This reduces battery swelling and allows for a longer battery life.
[0027] On the other hand, if the amount of positive electrode active material present within a given volume of the electrode is non-uniform, as shown in Figure 2B, the resulting electrode will likely experience variations in the voltage applied within the electrode when the battery is charged or discharged. Such an electrode will likely experience high voltages in certain areas, leading to the generation of gas due to decomposition of the electrolyte.
[0028] ·Composition formula (A) The precursor of this embodiment is preferably represented by the following composition formula (A): The compound represented by the following composition formula (A) is preferably an oxide or a hydroxide. Ni 1-x-y Co x M y O z (OH) 2-α ...Composition formula (A) (In composition formula (A), 0≦x≦0.45, 0≦y≦0.45, 0≦z≦3, and −0.5≦α≦2, and M is one or more metallic elements selected from the group consisting of Mg, Ca, Sr, Ba, Zn, B, Al, Mn, Ga, Ti, Zr, Ge, Fe, Cu, Cr, V, W, Mo, Sc, Y, Nb, La, Ta, Tc, Ru, Rh, Pd, Ag, Cd, In, and Sn.)
[0029] x x is preferably 0.01 or more, more preferably 0.02 or more, and even more preferably 0.03 or more. Furthermore, x is preferably 0.44 or less, more preferably 0.42 or less, and even more preferably 0.40 or less. The upper and lower limits of x can be arbitrarily combined. As an example of a combination, 0.01≦x≦0.44 is preferable, 0.02≦x≦0.42 is more preferable, and 0.03≦x≦0.40 is even more preferable.
[0030] ··y y is preferably 0.01 or more, more preferably 0.02 or more, and even more preferably 0.03 or more. Furthermore, y is preferably 0.44 or less, more preferably 0.42 or less, and even more preferably 0.40 or less. The upper and lower limits of y can be combined arbitrarily. As an example of a combination, 0.01≦y≦0.44 is preferable, 0.02≦y≦0.42 is more preferable, and 0.03≦y≦0.40 is even more preferable.
[0031] ··z z is preferably 0.1 or more, more preferably 0.2 or more, and even more preferably 0.3 or more. Furthermore, z is preferably 2.9 or less, more preferably 2.8 or less, and even more preferably 2.7 or less. The upper and lower limits of z can be arbitrarily combined. As an example of a combination, 0.1≦z≦2.9 is preferable, 0.2≦z≦2.8 is more preferable, and 0.3≦z≦2.7 is even more preferable.
[0032] α α is preferably −0.45 or more, more preferably −0.4 or more, and even more preferably −0.35 or more. In addition, α is preferably 1.8 or less, more preferably 1.6 or less, and even more preferably 1.4 or less. The upper and lower limit values of α can be arbitrarily combined. As an example of a combination, -0.45≦α≦1.8 is preferable, -0.4≦α≦1.6 is more preferable, and -0.35≦α≦1.4 is even more preferable.
[0033] x+y x+y is preferably greater than 0, more preferably 0.05 or greater and 0.70 or less, and even more preferably 0.10 or greater and 0.50 or less.
[0034] ··M In the composition formula (A), M is preferably one or more metal elements selected from the group consisting of Zr, Al, and Mn.
[0035] The composition of the precursor can be analyzed by dissolving the precursor powder in hydrochloric acid and then measuring the result using an ICP emission spectrometer. As an ICP emission spectrometer, for example, Optima 7300 manufactured by PerkinElmer Co., Ltd. can be used.
[0036] The precursor of this embodiment is D 50 The value of is preferably less than 10 μm, more preferably 9 μm or less, and even more preferably 8 μm or less. 50 The value of D of the precursor is preferably more than 1 μm, more preferably 2 μm or more, and even more preferably 3 μm or more. 50 When the particle size distribution of the positive electrode active material is less than the upper limit, the lithium compound reacts uniformly with the precursor in the subsequent calcination step, and a positive electrode active material having the same particle size distribution as the precursor is easily obtained. The use of such a positive electrode active material makes it easier to obtain a lithium secondary battery in which battery swelling is further suppressed. D 50 The upper and lower limits of the value can be combined arbitrarily. An example of a combination is D 50 The thickness is, for example, more than 1 μm and less than 10 μm, 2 μm or more and 9 μm or less, or 3 μm or more and 8 μm or less.
[0037] <Method of manufacturing a precursor for a positive electrode active material for a lithium secondary battery> A method for producing the precursor for a positive electrode active material of a lithium secondary battery according to this embodiment will be described. The process for producing the precursor includes a slurry preparation process in which a metal-containing aqueous solution containing at least nickel atoms and an alkaline aqueous solution are supplied to a reaction vessel to obtain a hydroxide-containing slurry, and a classification process in which the hydroxide-containing slurry is classified using a liquid cyclone classifier.
[0038] The method for producing the precursor preferably comprises a slurry preparation step, a classification step, and an optional reflux step, in this order. Each step will be described below.
[0039] [Slurry preparation process] The slurry preparation step is a step of supplying a metal-containing aqueous solution containing at least nickel atoms and an alkaline aqueous solution to a reaction vessel to obtain a hydroxide-containing slurry. In this step, a metal-containing aqueous solution containing at least nickel atoms and an alkaline aqueous solution are continuously supplied to a reaction vessel while being stirred, and reacted with each other to obtain a hydroxide-containing slurry. At this time, an aqueous solution containing an ammonium ion donor may be supplied.
[0040] Hereinafter, this step will be described using as an example a hydroxide-containing slurry a slurry containing a metal composite hydroxide containing nickel atoms, cobalt atoms, and aluminum atoms (sometimes referred to as nickel-cobalt-aluminum metal composite hydroxide).
[0041] First, a nickel salt solution, a cobalt salt solution, an aluminum salt solution, and a complexing agent are reacted by a coprecipitation method, particularly a continuous coprecipitation method described in JP-A-2002-201028, to obtain Ni 1-x-y Co x Al y A metal complex hydroxide represented by (OH)2 is produced.
[0042] The nickel salt that is the solute of the nickel salt solution is not particularly limited, but for example, any one or more of nickel sulfate, nickel nitrate, nickel chloride, and nickel acetate can be used.
[0043] As the cobalt salt that is the solute of the cobalt salt solution, for example, any one or more of cobalt sulfate, cobalt nitrate, cobalt chloride, and cobalt acetate can be used.
[0044] As the aluminum salt which is the solute of the aluminum salt solution, for example, aluminum sulfate or sodium aluminate can be used.
[0045] When producing a slurry containing a metal composite hydroxide containing manganese as the hydroxide-containing slurry, a manganese salt solution is used. In this case, the manganese salt that is the solute of the manganese salt solution can be, for example, one or more of manganese sulfate, manganese nitrate, manganese chloride, and manganese acetate.
[0046] The above metal salts are 1-x-y Co x Al y In other words, the molar ratio of nickel atoms in the solute of the nickel salt solution, cobalt atoms in the solute of the cobalt salt solution, and aluminum atoms in the solute of the aluminum salt solution is Ni 1-x-y Co x Al y The amount used is 1-xy:x:y corresponding to the composition ratio of (OH)2.
[0047] The solvent for the nickel salt solution, the cobalt salt solution, and the aluminum salt solution is preferably water.
[0048] The complexing agent is a compound capable of forming a complex with nickel ions, cobalt ions, and aluminum ions in an aqueous solution, and examples of the complexing agent include ammonium ion donors, hydrazine, ethylenediaminetetraacetic acid, nitrilotriacetic acid, uracildiacetic acid, and glycine. As the ammonium ion donor, for example, ammonium salts such as ammonium hydroxide, ammonium sulfate, ammonium chloride, ammonium carbonate, and ammonium fluoride can be used.
[0049] In the slurry preparation step, a complexing agent may or may not be used. In the present embodiment, when a complexing agent is used, the amount of the complexing agent contained in the mixed solution containing the nickel salt solution, the cobalt salt solution, the aluminum salt solution, and the complexing agent is, for example, such that the molar ratio of the amount of the complexing agent to the total number of moles of the metal salts is greater than 0 and less than or equal to 2.0.
[0050] In the coprecipitation method, to adjust the pH of the mixture containing the nickel salt solution, manganese salt solution, cobalt salt solution, aluminum salt solution, and complexing agent, an alkaline aqueous solution is added to the mixture before the pH of the mixture changes from alkaline to neutral. The alkaline aqueous solution can be sodium hydroxide or potassium hydroxide. The pH value in this specification is defined as the value measured when the temperature of the mixed solution is 40°C. The pH of the mixed solution is measured when the temperature of the mixed solution sampled from the reaction tank reaches 40°C. If the temperature of the sampled mixed liquid is lower than 40°C, heat the mixed liquid and measure the pH when it reaches 40°C. If the temperature of the sampled mixed liquid is higher than 40°C, cool the mixed liquid to 40°C and measure the pH.
[0051] During the reaction, the temperature of the reaction vessel is controlled within the range of, for example, 20°C or higher and 80°C or lower, preferably 30°C or higher and 70°C or lower.
[0052] During the reaction, the pH value in the reaction vessel is controlled within the range of, for example, pH 9 or more and pH 13 or less, preferably pH 11 or more and pH 13 or less.
[0053] The materials in the reaction vessel are mixed by suitable stirring. The reaction vessel used in the continuous coprecipitation method may be an overflow type reaction vessel in order to separate the formed metal composite hydroxide.
[0054] The reaction vessel may be in an inert atmosphere, which can prevent elements that are more easily oxidized than nickel from agglomerating, thereby making it possible to obtain a uniform metal composite hydroxide.
[0055] The reaction vessel may be in an oxygen-containing atmosphere or in the presence of an oxidizing agent. An oxygen-containing atmosphere having an appropriate amount of oxygen atoms can maintain an inert atmosphere in the reaction vessel. When the atmosphere in the reaction vessel is controlled by a gas species, a predetermined gas species may be passed through the reaction vessel or the reaction solution may be directly bubbled.
[0056] As the oxidizing agent, peroxides such as hydrogen peroxide, peroxide salts such as permanganate, perchlorates, hypochlorites, nitric acid, halogens, ozone, or the like can be used.
[0057] In addition, to improve uniformity within the reaction vessel and promote crystal growth of the precursor, it is preferable to stir the solution using a stirring blade installed in the reaction vessel. The physical properties of the precursor can be controlled by adjusting the rotation speed of the stirring blade. Although the stirring speed depends on the size of the reaction vessel, for example, the rotation speed of the stirring blade is preferably 300 rpm or more and 2000 rpm or less.
[0058] Through the above steps, a slurry containing nickel-cobalt-aluminum metal composite hydroxide is obtained as the hydroxide-containing slurry.
[0059] [Classification process] In this step, the hydroxide-containing slurry obtained in the above-mentioned slurry preparation step is classified using a liquid cyclone classifier.
[0060] The hydroxide-containing slurry is continuously extracted from the reaction vessel, stored in a slurry storage tank, and classified by a liquid cyclone classifier. Specifically, in the liquid cyclone classifier 40 shown in Fig. 3, among particles contained in the hydroxide-containing slurry fed from the direction indicated by the symbol Y, hydroxide-containing slurry A containing particles having a target particle diameter passes through the tapered portion 42 and is discharged from the bottom of the liquid cyclone classifier 40. Hydroxide-containing slurry B, which contains particles other than hydroxide-containing slurry A, is discharged from the top of the liquid cyclone classifier 40 along the direction indicated by the symbol X. Hydroxide-containing slurry A is recovered by the liquid cyclone classifier, and hydroxide-containing slurry B is continuously refluxed to the reaction vessel in the subsequent reflux step.
[0061] 3 is a schematic diagram of a liquid cyclone classifying device 40. The liquid cyclone classifying device 40 includes a cylindrical portion 41 and a tapered portion . First, the hydroxide-containing slurry is sent from the direction indicated by the symbol Y in Figure 3 and introduced into the liquid cyclone classifier. The hydroxide-containing slurry then undergoes rotational motion, exerting centrifugal force, which causes the particles contained in the hydroxide-containing slurry to be classified according to their particle diameters.
[0062] Due to centrifugal force, small particles gather at the center of the vortex and are discharged in the direction indicated by the symbol X along the upward flow generated at the center (indicated by the dashed arrow in Figure 3). Particles with large diameters gather on the outside of the vortex and are discharged in the direction indicated by the symbol Z by riding on the downward flow (solid arrow in Figure 3) generated on the outer wall.
[0063] In this embodiment, the taper angle θ of the tapered portion 42 of the liquid cyclone classifying device 40 is preferably 10° or more and 60° or less.
[0064] When the taper angle θ of the tapered portion 42 is equal to or greater than the lower limit, a sufficient centrifugal force is applied to the particles contained in the hydroxide-containing slurry, which increases the classification efficiency and makes it easier to obtain a precursor that satisfies the above requirements (1) to (3). Specifically, when the taper angle θ of the hydrocyclone classifier is increased, (D 50 -D 10 ) / D 30 The value of tends to be small, (D 90 -D 50 ) / D 70 The value of tends to be small, and [(D 50 -D 10 ) / D 30 ] / [(D50 -D 10 ) / D 30 ] tends to be close to 1. When the taper angle θ of the tapered portion 42 is equal to or less than the upper limit, it is possible to maintain a high discharge amount from the tapered portion 42. As a result, the number of particles contained in the hydroxide-containing slurry injected into the hydrocyclone classifier 40 is unlikely to increase, and it is possible to increase production efficiency while maintaining high classification efficiency.
[0065] The slurry flow rate of the liquid cyclone classifier is preferably 0.6 m / sec or more and 1.5 m / sec or less. The slurry flow rate refers to the actual measured value of the flow rate when the slurry is sent from the direction indicated by the symbol Y.
[0066] When the slurry flow rate of the hydrocyclone classifier is equal to or higher than the lower limit, a sufficient centrifugal force is applied to the particles contained in the hydroxide-containing slurry, which increases the classification efficiency and makes it easier to obtain a precursor that satisfies the above requirements (1) to (3). Specifically, when the slurry flow rate of the hydrocyclone classifier is increased, (D 50 -D 10 ) / D 30 The value of tends to be small, (D 90 -D 50 ) / D 70 The value of tends to be small, and [(D 50 -D 10 ) / D 30 ] / [(D 50 -D 10 ) / D 30 The value of ] tends to be close to 1. Furthermore, many particles are discharged from the tapered portion 42, which can increase the production efficiency of the precursor. When the slurry delivery flow rate of the liquid cyclone classifier is equal to or less than the above upper limit, excessively strong centrifugal force is unlikely to be applied to the particles contained in the hydroxide-containing slurry, and undesired particles with small particle diameters are unlikely to be discharged from the tapered section 42. This makes it easier to increase the classification efficiency and to obtain a precursor that satisfies the above requirements (1) to (3).
[0067] By carrying out the classification step and further setting the taper angle θ and the slurry flow rate within the above ranges, a precursor that satisfies the above requirements (1) to (3) can be obtained.
[0068] [Reflux process] The reflux step is a step of returning (refluxing) the hydroxide-containing slurry B classified by the liquid cyclone classifier in the classification step back into the reaction tank. The reflux method is not particularly limited, and known means can be used. For example, when returning the hydroxide-containing slurry B after classification directly to the reaction tank, it can be returned to the reaction tank by a pump. By repeating the classification step, reflux step, and particle growth in the reaction tank, the particles contained in hydroxide-containing slurry B can be allowed to continue growing until they reach the target particle diameter, making it easier to obtain a precursor that satisfies the above requirements (1) to (3).
[0069] The reflux rate, that is, the rate at which the hydroxide-containing slurry B is returned to the reaction vessel, may be adjusted according to the supply rates of the metal-containing aqueous solution and the aqueous solution containing the ammonium ion donor.
[0070] [Dehydration process] After the above reaction, the obtained hydroxide-containing slurry is washed and then dried to obtain a nickel-cobalt-aluminum metal composite hydroxide as a precursor.
[0071] When isolating the precursor, a method of dehydrating the hydroxide-containing slurry by centrifugation, suction filtration, or the like is preferred.
[0072] The precursor obtained by dehydration is preferably washed with a washing liquid containing water or an alkali. In this embodiment, washing with a washing liquid containing an alkali is preferred, and washing with a sodium hydroxide solution is more preferred.
[0073] [Drying process] The precursor obtained by the dehydration step is dried in an air atmosphere at a temperature of 105° C. to 200° C. for 1 hour to 20 hours.
[0074] In the above example, a metal composite hydroxide is produced as a precursor, but a metal composite oxide may also be prepared.
[0075] [Optional heating process] When producing a metal composite oxide as a precursor, it is preferable to have a step of heating the obtained metal composite hydroxide in an oxygen-containing atmosphere at a temperature in the range of 300° C. to 900° C. In this embodiment, it is preferable to heat for 1 hour to 20 hours.
[0076] The heating temperature is preferably 350°C or higher and 800°C or lower, and more preferably 400°C or higher and 700°C or lower. When the heating temperature is equal to or higher than the lower limit, the amount of metal composite hydroxide that may remain in the obtained precursor can be reduced. When the heating temperature is equal to or lower than the upper limit, sintering between precursor particles can be suppressed, and a precursor whose particle size distribution satisfies requirement (3) can be obtained.
[0077] <Method of manufacturing positive electrode active material for lithium secondary batteries> The method for producing a positive electrode active material of the present embodiment includes a mixing step of mixing the precursor obtained by the <Method for producing a precursor for a positive electrode active material of a lithium secondary battery> with a lithium compound to obtain a mixture, and a firing step of firing the obtained mixture.
[0078] [Mixing process] In this step, the precursor and the lithium compound are mixed to obtain a mixture.
[0079] Lithium compounds The lithium compound used in this embodiment may be any one of lithium carbonate, lithium nitrate, lithium acetate, lithium hydroxide, lithium oxide, lithium chloride, and lithium fluoride, or a mixture of two or more of these. Of these, either or both of lithium hydroxide and lithium carbonate are preferred.
[0080] A method for mixing the precursor of this embodiment with the lithium compound will be described below. The precursor and the lithium compound are mixed in consideration of the composition ratio of the final product. For example, when nickel-cobalt-aluminum metal composite hydroxide is used, the lithium compound and the metal composite hydroxide are mixed in the ratio of LiNi 1-x-y Co x Al y They are used in a ratio corresponding to the composition ratio of the lithium-nickel-cobalt-aluminum composite oxide represented by O2. When producing a lithium metal composite oxide containing an excess of lithium (a molar ratio exceeding 1), they are mixed in a ratio such that the molar ratio of the lithium contained in the lithium compound to the metal element contained in the metal composite hydroxide exceeds 1.
[0081] [Firing process] A lithium-nickel-cobalt-aluminum composite oxide can be obtained by calcining a mixture of a nickel-cobalt-aluminum metal composite hydroxide and a lithium compound. The calcination can be carried out in dry air, an oxygen atmosphere, an inert atmosphere, or the like, depending on the desired composition, and multiple heating steps can be carried out if necessary.
[0082] In this embodiment, the mixture may be fired in the presence of an inert flux. By firing in the presence of an inert flux, the reaction of the mixture can be promoted. The inert flux may remain in the positive electrode active material after firing, or may be removed by washing with water or alcohol after firing. In this embodiment, the positive electrode active material after firing is preferably washed with water or alcohol.
[0083] By adjusting the temperature maintained during firing, the particle size of the resulting positive electrode active material can be controlled.
[0084] The firing process may be a single firing or may include multiple firing steps. When multiple firing steps are performed, the firing step at the highest temperature is referred to as the main firing. Prior to the main firing, preliminary firing may be performed at a temperature lower than that of the main firing. Furthermore, after the main firing, post-firing may be performed at a temperature lower than that of the main firing.
[0085] The firing temperature (maximum holding temperature) in the main firing is preferably 600° C. or higher, more preferably 700° C. or higher, and particularly preferably 800° C. or higher, from the viewpoint of promoting the growth of particles of the positive electrode active material. Moreover, from the viewpoint of preventing cracks from forming in the particles of the positive electrode active material and maintaining the strength of the particles of the positive electrode active material, the firing temperature is preferably 1200° C. or lower, more preferably 1100° C. or lower, and particularly preferably 1000° C. or lower.
[0086] The upper and lower limits of the maximum holding temperature in the main firing can be arbitrarily combined. Examples of combinations include 600°C or higher and 1200°C or lower, 700°C or higher and 1100°C or lower, and 800°C or higher and 1000°C or lower.
[0087] The firing temperature of the pre-firing or post-firing may be lower than the firing temperature of the main firing, and may be, for example, in the range of 350°C or higher and 700°C or lower.
[0088] The temperature to be maintained during firing may be adjusted appropriately depending on the type of transition metal element, the type and amount of precipitating agent and inert fluxing agent used.
[0089] In this embodiment, the holding temperature can be set by taking into consideration the melting point of the inert melting agent described below, and it is preferable to set the holding temperature within the range of [melting point of inert melting agent - 200°C] or more and [melting point of inert melting agent + 200°C] or less.
[0090] The time for holding the temperature can be from 0.1 to 20 hours, preferably from 0.5 to 10 hours. The rate of temperature increase to the holding temperature is usually from 50°C / hour to 400°C / hour, and the rate of temperature decrease from the holding temperature to room temperature is usually from 10°C / hour to 400°C / hour. The firing atmosphere can be air, oxygen, nitrogen, argon, or a mixture thereof.
[0091] After the firing step, the mixture is crushed and sieved appropriately to obtain the positive electrode active material.
[0092] The inert flux that can be used in this embodiment is not particularly limited as long as it is unlikely to react with the mixture during firing. In this embodiment, examples of the inert flux include one or more elements selected from the group consisting of fluorides of one or more elements (hereinafter referred to as "A") selected from the group consisting of Na, K, Rb, Cs, Ca, Mg, Sr, and Ba, chlorides of A, carbonates of A, sulfates of A, nitrates of A, phosphates of A, hydroxides of A, molybdates of A, and tungstates of A.
[0093] Examples of fluorides of A include NaF (melting point: 993°C), KF (melting point: 858°C), RbF (melting point: 795°C), CsF (melting point: 682°C), CaF2 (melting point: 1402°C), MgF2 (melting point: 1263°C), SrF2 (melting point: 1473°C), and BaF2 (melting point: 1355°C).
[0094] Examples of chlorides of A include NaCl (melting point: 801°C), KCl (melting point: 770°C), RbCl (melting point: 718°C), CsCl (melting point: 645°C), CaCl (melting point: 782°C), MgCl (melting point: 714°C), SrCl (melting point: 857°C), and BaCl (melting point: 963°C).
[0095] Examples of carbonates of A include Na2CO3 (melting point: 854°C), K2CO3 (melting point: 899°C), Rb2CO3 (melting point: 837°C), Cs2CO3 (melting point: 793°C), CaCO3 (melting point: 825°C), MgCO3 (melting point: 990°C), SrCO3 (melting point: 1497°C), and BaCO3 (melting point: 1380°C).
[0096] Examples of sulfates of A include Na2SO4 (melting point: 884°C), K2SO4 (melting point: 1069°C), Rb2SO4 (melting point: 1066°C), Cs2SO4 (melting point: 1005°C), CaSO4 (melting point: 1460°C), MgSO4 (melting point: 1137°C), SrSO4 (melting point: 1605°C), and BaSO4 (melting point: 1580°C).
[0097] Nitrates of A include NaNO3 (melting point: 310°C), KNO3 (melting point: 337°C), RbNO3 (melting point: 316°C), CsNO3 (melting point: 417°C), Ca(NO3)2 (melting point: 561°C), Mg(NO3)2, Sr(NO3)2 (melting point: 645°C), and Ba(NO3)2 (melting point: 596°C).
[0098] Examples of phosphates of A include Na3PO4, K3PO4 (melting point: 1340°C), Rb3PO4, Cs3PO4, Ca3(PO4)2, Mg3(PO4)2 (melting point: 1184°C), Sr3(PO4)2 (melting point: 1727°C), and Ba3(PO4)2 (melting point: 1767°C).
[0099] Examples of hydroxides of A include NaOH (melting point: 318°C), KOH (melting point: 360°C), RbOH (melting point: 301°C), CsOH (melting point: 272°C), Ca(OH)2 (melting point: 408°C), Mg(OH)2 (melting point: 350°C), Sr(OH)2 (melting point: 375°C), and Ba(OH)2 (melting point: 853°C).
[0100] Examples of molybdates A include Na2MoO4 (melting point: 698°C), K2MoO4 (melting point: 919°C), Rb2MoO4 (melting point: 958°C), Cs2MoO4 (melting point: 956°C), CaMoO4 (melting point: 1520°C), MgMoO4 (melting point: 1060°C), SrMoO4 (melting point: 1040°C), and BaMoO4 (melting point: 1460°C).
[0101] Examples of tungstates A include Na2WO4 (melting point: 687°C), K2WO4, Rb2WO4, Cs2WO4, CaWO4, MgWO4, SrWO4, and BaWO4.
[0102] In this embodiment, two or more of these inactive fluxes may be used. When two or more of them are used, the melting point of the entire inactive flux may decrease.
[0103] Among these inert fluxes, one or more salts selected from the group consisting of carbonates of A, sulfates of A, and chlorides of A are preferred as inert fluxes for obtaining a positive electrode active material with higher crystallinity.
[0104] Furthermore, A is preferably either or both of sodium (Na) and potassium (K).
[0105] That is, among the above inert fluxes, particularly preferred inert fluxes are NaCl, KCl, Na2CO3, K2CO 3、 NaSO 4、 and K2SO4, and it is more preferable to use either or both of K2SO4 and Na2SO4.
[0106] In this embodiment, the amount of inert fluxing agent present during firing may be appropriately selected. For example, the amount of inert fluxing agent present during firing is preferably 0.1 parts by mass or more, more preferably 1 part by mass or more, per 100 parts by mass of the lithium compound. Furthermore, if it is necessary to promote particle growth of the positive electrode active material, an inert fluxing agent other than the inert fluxing agents listed above may be used in combination. Examples of inert fluxing agents used in this case include ammonium salts such as NH4Cl and NHF.
[0107] <Positive electrode active material for lithium secondary batteries> The positive electrode active material of this embodiment is obtained by using the precursor of this embodiment as a raw material and the above-mentioned <Method for producing a positive electrode active material for a lithium secondary battery>. When the positive electrode active material of this embodiment is used, a lithium secondary battery in which battery swelling is further suppressed is easily obtained.
[0108] In addition, the positive electrode active material of this embodiment is D 50 The value tends to be less than 10 μm.
[0109] <Lithium secondary battery> Next, the configuration of the lithium secondary battery will be described, along with a description of a positive electrode using the positive electrode active material for a lithium secondary battery produced by the above-described method, and a lithium secondary battery having this positive electrode.
[0110] The lithium secondary battery positive electrode active material used in producing the positive electrode of this embodiment is preferably made of the lithium secondary battery positive electrode active material of this embodiment, but may contain a positive electrode active material different from the lithium secondary battery positive electrode active material of this embodiment as long as the effects of the present invention are not impaired.
[0111] An example of the lithium secondary battery of this embodiment has a positive electrode, a negative electrode, a separator sandwiched between the positive electrode and the negative electrode, and an electrolyte solution disposed between the positive electrode and the negative electrode.
[0112] 1A and 1B are schematic diagrams showing an example of a lithium secondary battery of this embodiment. A cylindrical lithium secondary battery 10 of this embodiment is manufactured as follows.
[0113] First, as shown in FIG. 1A, a pair of strip-shaped separators 1, a strip-shaped positive electrode 2 having a positive electrode lead 21 at one end, and a strip-shaped negative electrode 3 having a negative electrode lead 31 at one end are stacked in this order: separator 1, positive electrode 2, separator 1, negative electrode 3, and then wound to form an electrode group 4.
[0114] 1B, an electrode group 4 and an insulator (not shown) are placed in a battery can 5, the bottom of the can is sealed, the electrode group 4 is impregnated with an electrolyte solution 6, and the electrolyte is disposed between the positive electrode 2 and the negative electrode 3. Furthermore, the top of the battery can 5 is sealed with a top insulator 7 and a sealing member 8, thereby producing a lithium secondary battery 10.
[0115] Examples of the shape of the electrode group 4 include a columnar shape such that the cross-sectional shape when the electrode group 4 is cut perpendicular to the winding axis is a circle, an ellipse, a rectangle, or a rectangle with rounded corners.
[0116] The shape of a lithium secondary battery having such an electrode group 4 can be any shape specified by IEC60086, a standard for batteries established by the International Electrotechnical Commission (IEC), or JIS C 8500. Examples of shapes that can be used include cylindrical and rectangular shapes.
[0117] Furthermore, the lithium secondary battery is not limited to the above-mentioned wound type configuration, and may be a laminated type configuration in which a laminated structure of a positive electrode, a separator, a negative electrode, and a separator is repeatedly stacked. Examples of laminated lithium secondary batteries include so-called coin type batteries, button type batteries, and paper type (or sheet type) batteries.
[0118] Each component will be described below in order. (positive electrode) The positive electrode of this embodiment can be manufactured by first preparing a positive electrode mixture containing a positive electrode active material, a conductive material, and a binder, and then supporting the positive electrode mixture on a positive electrode current collector.
[0119] (Conductive material) A carbon material can be used as the conductive material in the positive electrode of this embodiment. Examples of carbon materials include graphite powder, carbon black (e.g., acetylene black), and fibrous carbon materials. Because carbon black is a fine particle with a large surface area, adding a small amount of carbon black to the positive electrode mixture can increase the conductivity within the positive electrode and improve charge / discharge efficiency and output characteristics. However, adding too much carbon black reduces the binding strength between the binder and the positive electrode current collector, as well as the binding strength within the positive electrode mixture, which can actually increase internal resistance.
[0120] The proportion of the conductive material in the positive electrode mixture is preferably 5 to 20 parts by mass per 100 parts by mass of the positive electrode active material. When a fibrous carbon material such as graphitized carbon fiber or carbon nanotube is used as the conductive material, this proportion can be reduced.
[0121] (binder) The binder contained in the positive electrode of this embodiment can be a thermoplastic resin. The thermoplastic resin is polyvinylidene fluoride (hereinafter sometimes referred to as PVdF). fluororesins such as tetrafluoroethylene, polytetrafluoroethylene (hereinafter sometimes referred to as PTFE), tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride copolymer, hexafluoropropylene-vinylidene fluoride copolymer, and tetrafluoroethylene-perfluorovinyl ether copolymer; and polyolefin resins such as polyethylene and polypropylene.
[0122] Two or more of these thermoplastic resins may be mixed and used. By using a fluororesin and a polyolefin resin as binders and setting the proportion of the fluororesin to the entire positive electrode mixture to be 1% by mass or more and 10% by mass or less, and the proportion of the polyolefin resin to be 0.1% by mass or more and 2% by mass or less, a positive electrode mixture having high adhesion to the positive electrode current collector and high bonding strength within the positive electrode mixture can be obtained.
[0123] (Positive electrode current collector) The positive electrode current collector of the positive electrode of this embodiment can be a strip-shaped member made of a metal material such as Al, Ni, stainless steel, etc. Among them, a thin film made of Al is preferred because it is easy to process and inexpensive.
[0124] As a method for supporting the positive electrode mixture on the positive electrode current collector, a method of pressure molding the positive electrode mixture on the positive electrode current collector can be mentioned. Alternatively, the positive electrode mixture may be made into a paste using an organic solvent, and the resulting paste of the positive electrode mixture may be applied to at least one side of the positive electrode current collector, dried, and pressed to fix the positive electrode mixture on the positive electrode current collector.
[0125] When the positive electrode mixture is made into a paste, examples of the organic solvent that can be used include amine-based solvents such as N,N-dimethylaminopropylamine and diethylenetriamine; ether-based solvents such as tetrahydrofuran; ketone-based solvents such as methyl ethyl ketone; ester-based solvents such as methyl acetate; and amide-based solvents such as dimethylacetamide and N-methyl-2-pyrrolidone (hereinafter sometimes referred to as NMP).
[0126] Examples of methods for applying the positive electrode mixture paste to the positive electrode current collector include slit die coating, screen coating, curtain coating, knife coating, gravure coating, and electrostatic spraying.
[0127] The positive electrode can be produced by the above-mentioned methods. (Negative electrode) The negative electrode of the lithium secondary battery of this embodiment may be any electrode capable of doping and dedoping lithium ions at a potential lower than that of the positive electrode, and examples thereof include an electrode in which a negative electrode mixture containing a negative electrode active material is supported on a negative electrode current collector, and an electrode made of the negative electrode active material alone.
[0128] (Negative electrode active material) Examples of the negative electrode active material contained in the negative electrode include carbon materials, chalcogen compounds (oxides, sulfides, etc.), nitrides, metals, and alloys, which can be doped and dedoped with lithium ions at a lower potential than the positive electrode.
[0129] Examples of carbon materials that can be used as the negative electrode active material include graphite such as natural graphite and artificial graphite, cokes, carbon black, pyrolytic carbons, carbon fiber, and fired organic polymer compounds.
[0130] Oxides that can be used as negative electrode active materials include SiO2, SiO, and the like, which are compounds of the formula SiO x (where x is a positive real number); oxides of silicon such as TiO2 and TiO with the formula TiO x (where x is a positive real number); oxides of titanium, such as V2O5 and VO2, with the formula VO xVanadium oxides represented by (where x is a positive real number); iron oxides such as Fe3O4, Fe2O3, FeO, etc., of the formula FeO x Iron oxides represented by (where x is a positive real number); tin oxides such as SnO2, SnO, etc., of the formula SnO x Tin oxides represented by (where x is a positive real number); tungsten oxides such as WO3, WO2, etc., of the general formula WO x Tungsten oxides represented by (where x is a positive real number); composite metal oxides containing lithium and titanium or vanadium such as Li4Ti5O 12 , LiVO2, etc. can be mentioned.
[0131] Examples of sulfides that can be used as the negative electrode active material include titanium sulfides such as Ti2S3, TiS2, TiS, etc., of the formula TiS x Titanium sulfides represented by (where x is a positive real number); V3S4, VS 2、 VS, etc., of the formula VS x Vanadium sulfides represented by (where x is a positive real number); iron sulfides such as Fe3S4, FeS2, FeS, etc., of the formula FeS x Iron sulfides represented by (where x is a positive real number); molybdenum sulfides such as Mo2S3, MoS2, etc., of the formula MoS x Molybdenum sulfides represented by (where x is a positive real number); SnS 2、 SnS, etc., of the formula SnS x Tin sulfides represented by (where x is a positive real number); tungsten sulfides such as WS2, etc., of the formula WS x Tungsten sulfides represented by (where x is a positive real number); antimony sulfides such as Sb2S3, etc., of the formula SbS x Antimony sulfides represented by (where x is a positive real number); selenium sulfides such as Se5S3, SeS2, SeS, etc., of the formula SeS x Selenium sulfides represented by (where x is a positive real number) can be mentioned.
[0132] Examples of nitrides that can be used as the negative electrode active material include Li3N, Li 3-x A x N (where A is either one or both of Ni and Co, and 0 < x < 3). Lithium-containing nitrides such as this can be mentioned.
[0133] These carbon materials, oxides, sulfides, and nitrides may be used alone or in combination of two or more, and may be crystalline or amorphous.
[0134] Metals that can be used as the negative electrode active material include lithium metal, silicon metal, and tin metal.
[0135] Examples of alloys that can be used as the negative electrode active material include lithium alloys such as Li-Al, Li-Ni, Li-Si, Li-Sn, and Li-Sn-Ni; silicon alloys such as Si-Zn; tin alloys such as Sn-Mn, Sn-Co, Sn-Ni, Sn-Cu, and Sn-La; and alloys such as Cu2Sb and La3Ni2Sn7.
[0136] These metals and alloys are mainly used alone as electrodes after being processed into foils, for example.
[0137] Among the above-mentioned negative electrode active materials, carbon materials containing graphite as a main component, such as natural graphite or artificial graphite, are preferably used because the potential of the negative electrode hardly changes during charging from an uncharged state to a fully charged state (good potential flatness), the average discharge potential is low, and the capacity retention rate after repeated charge and discharge is high (good cycle characteristics). The shape of the carbon material may be, for example, flakes like natural graphite, spherical like mesocarbon microbeads, fibrous like graphitized carbon fiber, or an aggregate of fine powder.
[0138] The negative electrode mixture may contain a binder as needed. Examples of the binder include thermoplastic resins, specifically PVdF, thermoplastic polyimide, carboxymethyl cellulose, polyethylene, and polypropylene.
[0139] (Negative electrode current collector) The negative electrode current collector of the negative electrode can be a strip-shaped member made of a metal material such as Cu, Ni, stainless steel, etc. Among them, a thin film made of Cu is preferred because it is difficult to form an alloy with lithium and is easy to process.
[0140] As a method for supporting the negative electrode mixture on such a negative electrode current collector, as in the case of the positive electrode, there are a method using pressure molding, a method in which a paste is formed using a solvent or the like, which is applied to the negative electrode current collector, dried, and then pressed to bond the paste.
[0141] (separator) The separator of the lithium secondary battery of this embodiment can be made of, for example, a polyolefin resin such as polyethylene or polypropylene, a fluororesin, a nitrogen-containing aromatic polymer, or the like, and has the form of a porous film, nonwoven fabric, woven fabric, etc. The separator may be made of two or more of these materials, or may be made by laminating these materials.
[0142] In this embodiment, in order to allow good electrolyte permeation during use of the battery (during charging and discharging), the separator preferably has an air permeation resistance measured by the Gurley method defined in JIS P 8117 of 50 seconds / 100 cc or more and 300 seconds / 100 cc or less, and more preferably 50 seconds / 100 cc or more and 200 seconds / 100 cc or less.
[0143] The porosity of the separator is preferably 30% by volume or more and 80% by volume or less, more preferably 40% by volume or more and 70% by volume or less. The separator may be a laminate of separators with different porosities.
[0144] (electrolyte) The electrolyte solution of the lithium secondary battery of this embodiment contains an electrolyte and an organic solvent.
[0145] The electrolytes contained in the electrolyte solution are LiClO4, LiPF6, LiAsF6, LiSbF6, LiBF4, LiCF3SO3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(COCF3), Li(C4F9SO3), LiC(SO2CF3)3, Li2B 10 Cl 10 Examples of the electrolyte include lithium salts such as LiBOB (here, BOB stands for bis(oxalato)borate), LiFSI (here, FSI stands for bis(fluorosulfonyl)imide), lithium salts of lower aliphatic carboxylic acids, and LiAlCl4, and a mixture of two or more of these may also be used. Among these, it is preferable to use an electrolyte containing at least one selected from the group consisting of fluorine-containing LiPF6, LiAsF6, LiSbF6, LiBF4, LiCF3SO3, LiN(SO2CF3)2, and LiC(SO2CF3)3.
[0146] Examples of the organic solvent contained in the electrolytic solution include carbonates such as propylene carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, 4-trifluoromethyl-1,3-dioxolan-2-one, and 1,2-di(methoxycarbonyloxy)ethane; 1,2-dimethoxyethane, 1,3-dimethoxypropane, pentafluoropropyl methyl ether, 2,2,3,3-tetrafluoropropyl difluoromethyl ether, tetrahydrofuran, and 2-methyltetrahydrofuran. Ethers such as methyl ether, methyl acetone, γ-butyrolactone, etc.; esters such as methyl formate, methyl acetate, γ-butyrolactone, etc.; nitriles such as acetonitrile and butyronitrile; amides such as N,N-dimethylformamide and N,N-dimethylacetamide; carbamates such as 3-methyl-2-oxazolidone; sulfur-containing compounds such as sulfolane, dimethyl sulfoxide, 1,3-propane sultone, etc.; or organic solvents such as these with a fluoro group further introduced therein (organic solvents in which one or more hydrogen atoms have been replaced with fluorine atoms).
[0147] As the organic solvent, it is preferable to use a mixture of two or more of these. Among them, a mixed solvent containing a carbonate is preferable, and a mixed solvent of a cyclic carbonate and an acyclic carbonate and a mixed solvent of a cyclic carbonate and an ether are more preferable. As a mixed solvent of a cyclic carbonate and an acyclic carbonate, a mixed solvent containing ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate is preferable. An electrolyte solution using such a mixed solvent has many advantages, such as a wide operating temperature range, resistance to deterioration even when charged and discharged at a high current rate, resistance to deterioration even when used for a long period of time, and resistance to decomposition even when graphite materials such as natural graphite and artificial graphite are used as the negative electrode active material.
[0148] Furthermore, as the electrolyte, it is preferable to use an electrolyte containing a fluorine-containing lithium salt such as LiPF6 and an organic solvent having a fluorine substituent, because this increases the safety of the resulting lithium secondary battery. A mixed solvent containing an ether having a fluorine substituent, such as pentafluoropropyl methyl ether or 2,2,3,3-tetrafluoropropyl difluoromethyl ether, and dimethyl carbonate is even more preferable because it has a high capacity retention rate even when charging and discharging at a high current rate.
[0149] Furthermore, since the positive electrode having the above-described configuration contains the lithium secondary battery positive electrode active material having the above-described configuration, the amount of battery swelling of the lithium secondary battery can be suppressed.
[0150] <All-solid-state lithium-ion secondary battery> Next, the configuration of an all-solid-state lithium ion secondary battery will be described, along with a description of a positive electrode using the lithium secondary battery positive electrode active material produced according to this embodiment, and an all-solid-state lithium ion secondary battery having this positive electrode.
[0151] 4 and 5 are schematic diagrams showing an example of an all-solid-state lithium-ion secondary battery. Fig. 4 is a schematic diagram showing a laminate included in the all-solid-state lithium-ion secondary battery. Fig. 5 is a schematic diagram showing the overall configuration of the all-solid-state lithium-ion secondary battery.
[0152] The all-solid-state lithium-ion secondary battery 1000 includes a laminate 100 having a positive electrode 110, a negative electrode 120, and a solid electrolyte layer 130, and an exterior body 200 that houses the laminate 100. The materials constituting each member will be described later.
[0153] The laminate 100 may have an external terminal 113 connected to the positive electrode current collector 112 and an external terminal 123 connected to the negative electrode current collector 122 .
[0154] In the laminate 100, the positive electrode 110 and the negative electrode 120 sandwich the solid electrolyte layer 130 to prevent short-circuiting between them. Additionally, the all-solid-state lithium-ion secondary battery 1000 may have a separator between the positive electrode 110 and the negative electrode 120, such as is used in conventional liquid lithium-ion secondary batteries, to prevent short-circuiting between the positive electrode 110 and the negative electrode 120.
[0155] The all-solid-state lithium-ion secondary battery 1000 includes an insulator (not shown) that insulates the laminate 100 from the exterior body 200 , and a sealing body (not shown) that seals the opening 200 a of the exterior body 200 .
[0156] A container made of a highly corrosion-resistant metal material such as aluminum, stainless steel, nickel-plated steel, etc. can be used as exterior body 200. Alternatively, a container made of a laminate film processed into a bag shape with corrosion resistance on at least one surface can also be used.
[0157] The shape of the all-solid-state lithium ion secondary battery 1000 can be, for example, a coin type, a button type, a paper type (or a sheet type), a cylindrical type, or a rectangular type.
[0158] Although the all-solid-state lithium-ion secondary battery 1000 is illustrated as having one laminate 100, this is not limitative. The all-solid-state lithium-ion secondary battery 1000 may have a configuration in which the laminate 100 is used as a unit cell, and a plurality of unit cells (laminated bodies 100) are sealed inside an exterior body 200.
[0159] Each component will be described below in order.
[0160] (positive electrode) The positive electrode 110 includes a positive electrode active material layer 111 and a positive electrode current collector 112 .
[0161] The positive electrode active material layer 111 includes the above-described positive electrode active material for a lithium secondary battery according to one embodiment of the present invention. The positive electrode active material layer 111 may also include a solid electrolyte (second solid electrolyte), a conductive material, and a binder.
[0162] The positive electrode active material contained in the positive electrode active material layer 111 is in contact with a second solid electrolyte contained in the positive electrode active material layer 111. Specifically, the positive electrode active material layer 111 includes a plurality of particles (positive electrode active material) including lithium metal composite oxide crystals, and a solid electrolyte filled between the plurality of particles (positive electrode active material) and in contact with the particles (positive electrode active material).
[0163] (solid electrolyte) The solid electrolyte that may be included in the positive electrode active material layer 111 may be a solid electrolyte that has lithium ion conductivity and is used in known all-solid-state batteries. Examples of such solid electrolytes include inorganic electrolytes and organic electrolytes. Examples of inorganic electrolytes include oxide-based solid electrolytes, sulfide-based solid electrolytes, and hydride-based solid electrolytes. The organic electrolyte may be a polymer-based solid electrolyte.
[0164] In this embodiment, it is preferable to use an oxide-based solid electrolyte or a sulfide-based solid electrolyte, and it is more preferable to use an oxide-based solid electrolyte.
[0165] (Oxide solid electrolyte) Examples of oxide-based solid electrolytes include perovskite-type oxides, NASICON-type oxides, LISICON-type oxides, and garnet-type oxides.
[0166] As perovskite oxides, Lia La 1-a Li-La-Ti-based oxides such as LaTiO3 (0 < a < 1), Li b La 1-b Li-La-Ta-based oxides such as LaTaO3 (0 < b < 1), Li c La 1-c Li-La-Nb-based oxides such as LaNbO3 (0 < c < 1), etc. can be mentioned.
[0167] As NASICON-type oxides, Li 1+d Al d Ti 2-d (PO4)3 (0 ≤ d ≤ 1), etc. can be mentioned. NASICON-type oxides are oxides represented by Li m M 1 n M 2 o P p O q is an oxide represented by. In the formula, M 1 is one or more elements selected from the group consisting of B, Al, Ga, In, C, Si, Ge, Sn, Sb, and Se. In the formula, M 2 is one or more elements selected from the group consisting of Ti, Zr, Ge, In, Ga, Sn, and Al. In the formula, m, n, o, p, and q are arbitrary positive numbers.
[0168] As LISICON-type oxides, oxides represented by Li4MO4 - Li3MO4, etc., can be mentioned. 3 O4 - Li3M 4 O4, etc. can be mentioned. In the formula, M 3 is one or more elements selected from the group consisting of Si, Ge, and Ti. In the formula, M 4 is one or more elements selected from the group consisting of P, As, and V.The oxide-based solid electrolyte may be a crystalline material or an amorphous material. Examples of amorphous solid electrolytes include Li-BO compounds such as Li3BO3, Li2BO, and LiBO2. The oxide-based solid electrolyte preferably contains an amorphous material.
[0171] (Sulfide solid electrolyte) Sulfide-based solid electrolytes include Li2S-P2S5-based compounds, Li2S-SiS2-based compounds, Li2S-GeS2-based compounds, Li2S-B2S3-based compounds, Li2S-P2S3-based compounds, LiI-Si2S-P2S5, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, and Li 10 GeP2S 12 Examples include:
[0172] In this specification, the term "sulfide-based solid electrolyte" is used as a general term for solid electrolytes that primarily contain raw materials such as "LiS" and "P2S5" as described before "sulfide-based compound." For example, LiS-P2S5-based compounds include solid electrolytes that contain LiS and P2S5 and also contain other raw materials. LiS-P2S5-based compounds also include solid electrolytes with different mixing ratios of LiS and P2S5.
[0173] Li2S-P2S5 compounds include Li2S-P2S5, Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, and Li2S-P2S5-Z m S n (m and n are positive numbers; Z is Ge, Zn, or Ga).
[0174] Li2S-SiS2 compounds include Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li2SO4, and Li2S-SiS2-Li x MO y (x and y are positive numbers. M is P, Si, Ge, B, Al, Ga, or In).
[0175] Examples of Li2S-GeS2 based compounds include Li2S-GeS2 and Li2S-GeS2-P2S5.
[0176] The sulfide-based solid electrolyte may be a crystalline material or an amorphous material, and preferably includes an amorphous material.
[0177] (hydride-based solid electrolyte) Examples of hydride-based solid electrolyte materials include LiBH4, LiBH4-3KI, LiBH4-PI2, LiBH4-P2S5, LiBH4-LiNH2, 3LiBH4-LiI, LiNH2, Li2AlH6, Li(NH2)2I, Li2NH, LiGd(BH4)3Cl, Li2(BH4)(NH2), Li3(NH2)I, and Li4(BH4)(NH2)3.
[0178] Examples of polymer-based solid electrolytes include organic polymer electrolytes such as polyethylene oxide-based polymer compounds, and polymer compounds containing at least one selected from the group consisting of polyorganosiloxane chains and polyoxyalkylene chains.
[0179] Two or more solid electrolytes can be used in combination as long as the effects of the invention are not impaired.
[0180] (Conductive material) The conductive material that may be contained in the positive electrode active material layer 111 may be a carbon material or a metal compound. Examples of the carbon material include graphite powder, carbon black (e.g., acetylene black), and fibrous carbon materials. Carbon black is a fine particle with a large surface area. Therefore, adding an appropriate amount of carbon black to the positive electrode active material layer 111 can increase the internal conductivity of the positive electrode 110 and improve the charge / discharge efficiency and output characteristics. On the other hand, if too much carbon black is added, the adhesive strength between the positive electrode active material layer 111 and the positive electrode current collector 112 and the adhesive strength within the positive electrode active material layer 111 will decrease, which will instead cause an increase in internal resistance. The metal compounds include electrically conductive metals, metal alloys and metal oxides.
[0181] In the case of a carbon material, the proportion of the conductive material in the positive electrode active material layer 111 is preferably 5 parts by mass or more and 20 parts by mass or less per 100 parts by mass of the positive electrode active material. When a fibrous carbon material such as graphitized carbon fiber or carbon nanotube is used as the conductive material, this proportion can be reduced.
[0182] (binder) When the positive electrode active material layer 111 contains a binder, a thermoplastic resin can be used as the binder. Examples of the thermoplastic resin include fluororesins such as polyimide resins, polyvinylidene fluoride (hereinafter sometimes referred to as PVdF), polytetrafluoroethylene, tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride copolymers, hexafluoropropylene-vinylidene fluoride copolymers, and tetrafluoroethylene-perfluorovinyl ether copolymers; and polyolefin resins such as polyethylene and polypropylene. Hereinafter, polyvinylidene fluoride may be referred to as PVdF, and polytetrafluoroethylene may be referred to as PTFE.
[0183] Two or more of these thermoplastic resins may be mixed and used. By using a fluororesin and a polyolefin resin as binders and setting the proportion of the fluororesin to the entire positive electrode active material layer 111 to be 1% by mass or more and 10% by mass or less and the proportion of the polyolefin resin to be 0.1% by mass or more and 2% by mass or less, the positive electrode active material layer 111 has high adhesion between the positive electrode current collector 112 and the positive electrode current collector 112, and high bonding strength within the positive electrode active material layer 111.
[0184] The positive electrode active material layer 111 may be formed in advance into a sheet-like molded body containing a positive electrode active material and used as an "electrode" in the present invention. In the following description, such a sheet-like molded body may be referred to as a "positive electrode active material sheet." A laminate formed by laminating a current collector on a positive electrode active material sheet may also be used as an electrode.
[0185] The positive electrode active material sheet may contain at least one selected from the group consisting of the above-mentioned solid electrolyte, conductive material, and binder.
[0186] The positive electrode active material sheet can be obtained, for example, by mixing a positive electrode active material, a sintering aid, the above-mentioned conductive material, the above-mentioned binder, a plasticizer, and a solvent to prepare a slurry, and then applying the obtained slurry onto a carrier film and drying it.
[0187] As the sintering aid, for example, Li3BO3 or Al2O3 can be used.
[0188] As the plasticizer, for example, dioctyl phthalate can be used.
[0189] As the solvent, for example, acetone, ethanol, or N-methyl-2-pyrrolidone can be used.
[0190] When preparing the slurry, a ball mill can be used for mixing. The resulting mixture often contains air bubbles that were mixed in during mixing, so it is recommended to degas it by reducing the pressure. When degassing, part of the solvent volatilizes and concentrates, increasing the viscosity of the slurry.
[0191] The slurry can be applied using a known doctor blade.
[0192] The carrier film may be a PET film.
[0193] The cathode active material sheet obtained after drying is peeled off from the carrier film and processed into a required shape by appropriate punching for use. The cathode active material sheet may also be uniaxially pressed in the thickness direction as appropriate.
[0194] (Positive electrode current collector) The positive electrode current collector 112 of the positive electrode 110 can be a sheet-like member made of a metal material such as Al, Ni, stainless steel, or Au. Among these, a thin film made of Al is preferred because it is easy to process and inexpensive.
[0195] A method for supporting the positive electrode active material layer 111 on the positive electrode current collector 112 includes a method of pressure molding the positive electrode active material layer 111 on the positive electrode current collector 112. Cold pressing or hot pressing can be used for pressure molding.
[0196] Alternatively, a mixture of a positive electrode active material, a solid electrolyte, a conductive material, and a binder may be made into a paste using an organic solvent to form a positive electrode mixture, and the resulting positive electrode mixture may be applied to at least one side of the positive electrode current collector 112, dried, and pressed to adhere the mixture, thereby causing the positive electrode active material layer 111 to be supported on the positive electrode current collector 112.
[0197] Alternatively, a mixture of a positive electrode active material, a solid electrolyte, and a conductive material may be made into a paste using an organic solvent to form a positive electrode mixture, and the resulting positive electrode mixture may be applied to at least one side of the positive electrode current collector 112, dried, and sintered to cause the positive electrode active material layer 111 to be supported on the positive electrode current collector 112.
[0198] Examples of organic solvents that can be used in the positive electrode mixture include amine solvents such as N,N-dimethylaminopropylamine and diethylenetriamine, ether solvents such as tetrahydrofuran, ketone solvents such as methyl ethyl ketone, ester solvents such as methyl acetate, and amide solvents such as dimethylacetamide and N-methyl-2-pyrrolidone. Hereinafter, N-methyl-2-pyrrolidone may be referred to as NMP.
[0199] Examples of methods for applying the positive electrode mixture to the positive electrode current collector 112 include slit die coating, screen coating, curtain coating, knife coating, gravure coating, and electrostatic spraying.
[0200] The positive electrode 110 can be produced by the methods listed above.
[0201] (Negative electrode) The negative electrode 120 has a negative electrode active material layer 121 and a negative electrode current collector 122. The negative electrode active material layer 121 contains a negative electrode active material. The negative electrode active material layer 121 may also contain a solid electrolyte and a conductive material. The solid electrolyte, the conductive material, and the binder may be the same as those described above.
[0202] (Negative electrode active material) Examples of the negative electrode active material contained in the negative electrode active material layer 121 include carbon materials, chalcogen compounds (oxides, sulfides, etc.), nitrides, metals, and alloys, which can be doped and dedoped with lithium ions at a lower potential than the positive electrode 110.
[0203] Examples of carbon materials that can be used as the negative electrode active material include graphite such as natural graphite and artificial graphite, cokes, carbon black, pyrolytic carbons, carbon fiber, and fired organic polymer compounds.
[0204] Oxides that can be used as negative electrode active materials include SiO2, SiO, and the like, which are compounds of the formula SiO x (where x is a positive real number); oxides of silicon such as TiO2 and TiO with the formula TiO xTitanium oxides represented by (where x is a positive real number); vanadium oxides represented by VO such as V2O5 and VO2 x Vanadium oxides represented by (where x is a positive real number); iron oxides represented by FeO such as Fe3O4, Fe2O3, and FeO x Iron oxides represented by (where x is a positive real number); tin oxides represented by SnO such as SnO2 and SnO x Tin oxides represented by (where x is a positive real number); tungsten oxides represented by the general formula WO such as WO3 and WO2 x Tungsten oxides represented by (where x is a positive real number); metal composite oxides containing lithium and titanium or lithium and vanadium such as Li4Ti5O 12 , LiVO2, etc. can be mentioned.
[0205] Sulfides that can be used as negative electrode active materials include titanium sulfides represented by the formula TiS such as Ti2S3, TiS2, and TiS x Titanium sulfides represented by (where x is a positive real number); vanadium sulfides represented by VS such as V3S4 and VS 2、 Vanadium sulfides represented by the formula VS such as VS x Vanadium sulfides represented by (where x is a positive real number); iron sulfides represented by FeS such as Fe3S4, FeS2, and FeS x Iron sulfides represented by (where x is a positive real number); molybdenum sulfides represented by MoS such as Mo2S3 and MoS2 x Molybdenum sulfides represented by (where x is a positive real number); tin sulfides represented by SnS such as SnS 2、 Tin sulfides represented by the formula SnS such as SnS x Tin sulfides represented by (where x is a positive real number); tungsten sulfides represented by WS such as WS2 x Tungsten sulfides represented by (where x is a positive real number); antimony sulfides represented by SbS such as Sb2S3 x Antimony sulfides represented by (where x is a positive real number); selenium sulfides represented by SeS such as Se5S3, SeS2, and SeS x Selenium sulfides represented by (where x is a positive real number) can be mentioned.
[0206] Nitrides that can be used as negative electrode active materials include lithium-containing nitrides such as Li3N, Li 3-x A x N (where A is either Ni or Co or both, and 0 < x < 3).
[0207] These carbon materials, oxides, sulfides, and nitrides may be used alone or in combination of two or more, and may be crystalline or amorphous.
[0208] Examples of metals that can be used as the negative electrode active material include lithium metal, silicon metal, and tin metal.
[0209] Examples of alloys that can be used as the negative electrode active material include lithium alloys such as Li-Al, Li-Ni, Li-Si, Li-Sn, and Li-Sn-Ni; silicon alloys such as Si-Zn; tin alloys such as Sn-Mn, Sn-Co, Sn-Ni, Sn-Cu, and Sn-La; and alloys such as Cu2Sb and La3Ni2Sn7.
[0210] These metals and alloys are mainly used alone as electrodes after being processed into foils, for example.
[0211] Among the above-mentioned negative electrode active materials, carbon materials containing graphite as a main component, such as natural graphite or artificial graphite, are preferably used because the potential of the negative electrode 120 changes little from an uncharged state to a fully charged state during charging (good potential flatness), the average discharge potential is low, and the capacity retention rate after repeated charge and discharge is high (good cycle characteristics). The shape of the carbon material may be, for example, flakes like natural graphite, spherical like mesocarbon microbeads, fibrous like graphitized carbon fiber, or an aggregate of fine powder.
[0212] Among the above negative electrode active materials, oxides are preferably used because they have high thermal stability, are less likely to form dendrites due to Li metal, etc. The oxides are preferably in the form of fibers or aggregates of fine powder.
[0213] (Negative electrode current collector) The negative electrode current collector 122 of the negative electrode 120 can be a strip-shaped member made of a metal material such as Cu, Ni, stainless steel, etc. Among these, a thin film made of Cu is preferred because it is difficult to form an alloy with lithium and is easy to process.
[0214] As in the case of the positive electrode 110, methods for supporting the negative electrode active material layer 121 on the negative electrode current collector 122 include a pressure molding method, a method in which a paste-like negative electrode mixture containing a negative electrode active material is applied to the negative electrode current collector 122, dried, and then pressed to bond the layer, and a method in which a paste-like negative electrode mixture containing a negative electrode active material is applied to the negative electrode current collector 122, dried, and then sintered.
[0215] (solid electrolyte layer) The solid electrolyte layer 130 has the above-mentioned solid electrolyte (first solid electrolyte). When the positive electrode active material layer 111 contains a solid electrolyte, the solid electrolyte (first solid electrolyte) constituting the solid electrolyte layer 130 and the solid electrolyte (second solid electrolyte) contained in the positive electrode active material layer 111 may be the same material. The solid electrolyte layer 130 functions as a medium for transmitting lithium ions, and also functions as a separator that separates the positive electrode 110 and the negative electrode 120 and prevents short circuits.
[0216] The solid electrolyte layer 130 can be formed by depositing an inorganic solid electrolyte on the surface of the positive electrode active material layer 111 of the above-mentioned positive electrode 110 by sputtering.
[0217] The solid electrolyte layer 130 can be formed by applying a paste mixture containing a solid electrolyte to the surface of the positive electrode active material layer 111 of the above-described positive electrode 110, and then drying the mixture. After drying, the mixture may be press-molded and further pressed by cold isostatic pressing (CIP) to form the solid electrolyte layer 130.
[0218] Furthermore, the solid electrolyte layer 130 can be formed by first forming the solid electrolyte into pellets, stacking the solid electrolyte pellets on the above-mentioned positive electrode active material sheet, and uniaxially pressing them in the stacking direction. The positive electrode active material sheet becomes the positive electrode active material layer 111.
[0219] The resulting laminate of the positive electrode active material layer 111 and the solid electrolyte layer 130 is further laminated with a positive electrode current collector 112 on the positive electrode active material layer 111. The laminate is uniaxially pressed in the lamination direction and then sintered to form the solid electrolyte layer 130 and the positive electrode 110.
[0220] Such a positive electrode 110 is in contact with the solid electrolyte layer 130. The solid electrolyte layer 130 includes a first solid electrolyte.
[0221] The positive electrode 110 includes a positive electrode active material layer 111 in contact with the solid electrolyte layer 130, and a positive electrode current collector 112 on which the positive electrode active material layer 111 is stacked. The positive electrode active material layer 111 includes a plurality of particles containing lithium metal composite oxide crystals (i.e., a positive electrode active material according to one embodiment of the present invention), and a solid electrolyte (a second solid electrolyte) filled between the plurality of particles and in contact with the particles.
[0222] The solid electrolyte and particles contained in the positive electrode active material layer 111 are in contact with the solid electrolyte layer 130. That is, the particles contained in the positive electrode active material layer 111 are in contact with the solid electrolyte contained in the positive electrode active material layer 111 and the solid electrolyte layer 130.
[0223] It is not necessary that all of the particles (positive electrode active material) contained in the positive electrode active material layer 111 be in contact with the solid electrolyte contained in the positive electrode active material layer 111 and the solid electrolyte layer 130.
[0224] The positive electrode active material contained in the positive electrode active material layer 111 comes into contact with the solid electrolyte contained in the positive electrode active material layer 111, thereby establishing electrical conduction with the solid electrolyte contained in the positive electrode active material layer 111. Furthermore, the positive electrode active material contained in the positive electrode active material layer 111 comes into contact with the solid electrolyte layer 130, thereby establishing electrical conduction with the solid electrolyte layer 130. Furthermore, the solid electrolyte contained in the positive electrode active material layer 111 comes into contact with the solid electrolyte layer 130, thereby establishing electrical conduction with the solid electrolyte layer 130.
[0225] As a result, the positive electrode active material contained in the positive electrode active material layer 111 is electrically connected to the solid electrolyte layer 130 directly or indirectly.
[0226] The laminate 100 can be produced by laminating the negative electrode 120, using a known method, on the solid electrolyte layer 130 provided on the positive electrode 110 as described above, in such a manner that the negative electrode electrolyte layer 121 contacts the surface of the solid electrolyte layer 130. This brings the solid electrolyte layer 130 into contact with the negative electrode active material layer 121 and provides electrical conduction.
[0227] As described above, the obtained all-solid-state lithium-ion secondary battery 100 is provided by bringing the solid electrolyte layer 130 into contact with the positive electrode 110 and the negative electrode 120 so as to prevent short-circuiting between the positive electrode 110 and the negative electrode 120. The provided all-solid-state lithium-ion battery 100 is charged by connecting it to an external power source and applying a negative potential to the positive electrode 110 and a positive potential to the negative electrode 120.
[0228] Furthermore, the charged all-solid-state lithium-ion secondary battery 100 is discharged by connecting a discharge circuit to the positive electrode 110 and the negative electrode 120 and passing current through the discharge circuit.
[0229] The positive electrode active material having the above-described configuration allows smooth transfer of lithium ions between the positive electrode and the solid electrolyte, thereby improving battery performance.
[0230] According to the electrode having the above-described configuration, since it contains the above-described positive electrode active material, it is possible to improve the battery performance of the all-solid-state lithium ion battery. [Example]
[0231] Next, the present invention will be described in more detail with reference to examples.
[0232] <Composition analysis> The composition of the precursor for the positive electrode active material of a lithium secondary battery produced by the method described below was analyzed by dissolving the obtained powder of the precursor for the positive electrode active material of a lithium secondary battery in hydrochloric acid and then using an ICP optical emission spectrometer (Optima 7300, manufactured by PerkinElmer Co., Ltd.).
[0233] <Measurement of particle size distribution> The cumulative volume particle size distribution of the precursor was measured by a laser diffraction scattering method using a particle size distribution measuring device LA-950 manufactured by Horiba, Ltd., under the measurement conditions shown in Table 1 below.
[0234] Then, in the obtained cumulative particle size distribution curve, the particle diameter (μm) at which the cumulative volume ratio from the small particle side becomes 10% is defined as D 10 , the particle diameter (μm) at 30% is D 30 , the particle diameter (μm) at 50% is D 50 , the particle diameter (μm) at 70% is D 70 , 90% particle diameter (μm) is D 90 When the above D 10 , the D 30 , the D 50 , the D 70 , and the D 90 Using the value of (D 50 -D 10 ) / D 30 , (D 90 -D 50 ) / D 70 , and [(D 50 -D 10 ) / D 30 ] / [(D 90 -D 50 ) / D 70 ] values were calculated.
[0235] [Table 1]
[0236] <Preparation of positive electrode> A positive electrode active material for a lithium secondary battery obtained by the manufacturing method described below, a conductive material (acetylene black), and a binder (PVdF) were mixed and kneaded in a ratio of 92:5:3 (mass ratio) of the positive electrode active material for a lithium secondary battery:conductive material:binder, to prepare a paste-like positive electrode mixture. N-methyl-2-pyrrolidone was used as the organic solvent when preparing the positive electrode mixture.
[0237] The obtained positive electrode mixture was applied to an Al foil having a thickness of 40 μm, which served as a current collector, and then vacuum dried at 150° C. for 8 hours to obtain a positive electrode.
[0238] <Preparation of negative electrode> Next, artificial graphite (MAGD manufactured by Hitachi Chemical Co., Ltd.) as a negative electrode active material, CMC (manufactured by Daiichi Kogyoyaku Co., Ltd.) and SBR (manufactured by Nippon A&L Inc.) as binders were added and kneaded in a ratio of negative electrode active material:CMC:SBR=98:1:1 (mass ratio) to prepare a paste-like negative electrode mixture. Ion-exchanged water was used as the solvent when preparing the negative electrode mixture.
[0239] The obtained negative electrode mixture was applied to a Cu foil having a thickness of 12 μm, which served as a current collector, and then vacuum dried at 60° C. for 8 hours to obtain a negative electrode.
[0240] <Fabrication of lithium secondary batteries (laminated cells)> The positive electrode prepared in <Preparation of the positive electrode> was placed on an aluminum laminate film with the aluminum foil side facing down, and a laminated film separator (a porous polyethylene film (thickness 27 μm)) was placed on top of that. Next, the negative electrode prepared in <Preparation of the negative electrode> was placed on top of the laminated film separator with the copper foil side facing up, and an aluminum laminate film was placed on top of that. The assembly was then heat-sealed, leaving an area for the electrolyte to be injected. The assembly was then moved to a dry bench with a dew point temperature of -50°C or below, and 1 mL of electrolyte was injected using a vacuum injection machine. The electrolyte was prepared by adding 1 vol% vinylene carbonate to a 16:10:74 (volume ratio) mixture of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate, and dissolving LiPF6 at a ratio of 1.3 mol / L. Finally, the electrolyte injection portion was heat-sealed to prepare a laminate cell.
[0241] [Measurement of battery swelling] The amount of battery swelling was measured by the following method. First, after the formation of the laminate cell produced as described above, the volume of the laminate cell was measured by Archimedes' method after discharging to 2.5 V at a current value of 0.2 CA, and the volume before storage was measured. Thereafter, the battery was charged to 4.3 V and stored in a thermostatic chamber at 60°C for 7 days. After storage, the laminated cell was discharged to 2.5 V at a current value of 0.2 CA, and the volume of the laminated cell was measured by Archimedes' method to determine the volume after storage. Volume difference before and after storage (cm 3 ) by the amount of positive electrode material (g) present in the laminate cell to obtain the battery swelling amount per positive electrode material (cm 3 / g).
[0242] The Archimedes method is a method for measuring the actual volume of the entire laminate cell from the difference between the weight of the laminate cell in air and the weight of the laminate cell in water using an automatic hydrometer. The formation of laminated cells was carried out under the following conditions. Formation conditions: Charged to 10% SOC at 0.1 CA at a test temperature of 25°C, left at a test temperature of 60°C for 10 hours, then charged to 4.3 V at 0.1 CA using CC-CV charging at a test temperature of 25°C until the current reached 0.05 CA. Further discharged to 2.5 V at 0.2 CA, and then performed two charge / discharge cycles at 0.2 CA.
[0243] Example 1 Slurry preparation process Water was placed in a 500 L cylindrical reaction vessel equipped with an agitator equipped with a 220φ propeller-type agitating blade and an overflow pipe, and then a 32 mass % sodium hydroxide solution was added until the pH reached 12.4 (measured when the solution temperature was 40°C), and the temperature was maintained at 40°C with a heater. Next, nitrogen gas was continuously blown into the reaction vessel at a flow rate of 5 L / min to make the atmosphere inside the reaction vessel an inert atmosphere.
[0244] A nickel sulfate solution and a cobalt sulfate solution were mixed in an atomic ratio of nickel to cobalt atoms of 92.8:7.2 to prepare a mixed raw material solution, which was continuously fed into a reaction vessel at a constant rate. A 0.76 mol / L ammonium sulfate solution was used as a complexing agent, and the ammonia concentration was continuously fed into the reaction vessel at a constant rate of 0.23 mol / L. Next, a 54% by mass aluminum sulfate solution was added at a flow rate adjusted to a ratio of nickel to cobalt to aluminum atoms of 90:7:3. Furthermore, 32% by mass sodium hydroxide was intermittently added to maintain the pH of the solution in the reaction vessel at 12.4 (measured when the solution temperature was 40°C).
[0245] The nickel-cobalt-aluminum metal composite hydroxide-containing slurry obtained by the above reaction was stored in a slurry storage tank through an overflow pipe.
[0246] ·Classification process Next, the nickel-cobalt-aluminum metal composite hydroxide-containing slurry stored in the slurry storage tank was introduced into a wet classifier liquid cyclone (T-10B-1 model, manufactured by Murata Industries, Ltd.) with a taper angle θ of 16° as shown in Figure 3, at a slurry flow rate of 0.84 m / s.
[0247] The nickel-cobalt-aluminum metal composite hydroxide-containing slurry discharged from the bottom of the wet classifier liquid cyclone was classified and recovered.
[0248] Reflux process The nickel-cobalt-aluminum metal composite hydroxide-containing slurry discharged from the top of the wet classifier hydrocyclone was repeatedly returned to the reaction tank. The nickel-cobalt-aluminum metal composite hydroxide-containing slurry in the slurry storage tank was returned to the reaction tank while being dehydrated as appropriate.
[0249] The obtained nickel-cobalt-aluminum metal composite hydroxide was washed and dehydrated, then dried at 105°C for 20 hours and sieved, and the particle size distribution and composition were analyzed. The composition formula of the obtained nickel-cobalt-aluminum metal composite hydroxide was Ni 90.2 Co 7.0 Al 2.8 (OH) 2.1 It was.
[0250] The nickel-cobalt-aluminum metal composite hydroxide and lithium hydroxide powder were weighed and mixed in a molar ratio of Li / (Ni+Co+Al)=1.15 to obtain a mixture. The resulting mixture was then baked in an oxygen atmosphere at 760°C for 5 hours, washed, dehydrated, and dried to obtain a positive electrode active material for a lithium secondary battery. A laminate cell was fabricated using the resulting positive electrode active material for a lithium secondary battery, and the amount of battery swelling was measured. The results are shown in Table 2.
[0251] Example 2 Slurry preparation process Water was placed in a 500 L cylindrical reaction vessel equipped with an agitator equipped with a 220φ propeller-type agitating blade and an overflow pipe, and then a 32 mass % sodium hydroxide solution was added until the pH reached 11.0 (measured when the solution temperature was 40°C), and the temperature was maintained at 60°C with a heater. Next, nitrogen gas was continuously blown into the reaction vessel at a flow rate of 5 L / min to make the atmosphere inside the reaction vessel an inert atmosphere.
[0252] A mixed raw material solution was prepared by mixing an aqueous nickel sulfate solution, an aqueous cobalt sulfate solution, and an aqueous manganese sulfate solution in an atomic ratio of nickel atoms, cobalt atoms, and manganese atoms of 88:9:3. The mixed raw material solution was continuously fed into a reaction vessel at a constant rate. A 0.76 mol / L ammonium sulfate solution was used as a complexing agent, and the ammonia concentration was continuously fed into the reaction vessel at a constant rate of 0.07 mol / L. Furthermore, 32% by mass of sodium hydroxide was intermittently added to maintain the pH of the solution in the reaction vessel at 11.0 (measured when the solution temperature was 40°C).
[0253] The nickel-cobalt-manganese metal composite hydroxide-containing slurry obtained by the above reaction was stored in a slurry storage tank through an overflow pipe.
[0254] ·Classification process Next, the nickel-cobalt-manganese metal composite hydroxide-containing slurry stored in the slurry storage tank was introduced into a wet classifier liquid cyclone (Murata Industries, Ltd., T-10B-1 model, taper angle θ: 16°) at a liquid cyclone flow rate of 0.47 m / s.
[0255] The nickel-cobalt-manganese metal composite hydroxide-containing slurry discharged from the bottom of the wet classifier liquid cyclone was classified and recovered.
[0256] Reflux process The nickel-cobalt-manganese metal composite hydroxide-containing slurry discharged from the top of the wet classifier hydrocyclone was repeatedly returned to the reaction tank. The nickel-cobalt-manganese metal composite hydroxide-containing slurry in the slurry storage tank was returned to the reaction tank while being dehydrated as appropriate.
[0257] The obtained nickel-cobalt-manganese metal composite hydroxide was washed and dehydrated, then dried at 105°C for 20 hours and sieved, and the particle size distribution and composition were analyzed. The composition formula of the obtained nickel-cobalt-manganese metal composite hydroxide was Ni 88.3 Co 8.9 Mn 2.8 (OH) 2.0 It was.
[0258] A laminate cell was produced using the lithium secondary battery positive electrode active material obtained in the same manner as in Example 1, except that the nickel-cobalt-manganese metal composite hydroxide was used, and the amount of battery swelling was measured. The results are shown in Table 2.
[0259] (Comparative Example 1) Slurry preparation process Water was placed in a 500 L cylindrical reaction vessel equipped with an agitator equipped with a 220φ propeller-type agitating blade and an overflow pipe, and then a 32 mass % sodium hydroxide solution was added until the pH reached 12.0 (measured when the solution temperature was 40°C), and the temperature was maintained at 40°C with a heater. Next, nitrogen gas was continuously blown into the reaction vessel at a flow rate of 5 L / min to make the atmosphere inside the reaction vessel an inert atmosphere.
[0260] A nickel sulfate solution and a cobalt sulfate solution were mixed in an atomic ratio of 92.8:7.2 to prepare a mixed raw material solution, which was then continuously fed into a reaction vessel at a constant rate. A 0.76 mol / L ammonium sulfate solution was used as a complexing agent, and the ammonia concentration was continuously fed into the reaction vessel at a constant rate of 0.23 mol / L. A 10.8% by mass aluminum sulfate solution was added at a flow rate adjusted to obtain an atomic ratio of nickel, cobalt, and aluminum atoms of 90:7:3. Furthermore, 32% by mass sodium hydroxide was intermittently added to maintain the pH of the solution in the reaction vessel at 12.0 (measured when the solution temperature was 40°C).
[0261] The obtained nickel-cobalt-aluminum metal composite hydroxide was washed and dehydrated, then dried at 105°C for 20 hours and sieved, and the particle size distribution and composition were analyzed. The composition formula of the obtained nickel-cobalt-aluminum metal composite hydroxide was Ni 90.1 Co 6.8 Al 3.1 (OH) 2.1 It was.
[0262] A laminate cell was produced using the positive electrode active material for a lithium secondary battery obtained in the same manner as in Example 1, except that the nickel-cobalt-aluminum metal composite hydroxide was used, and the amount of battery swelling was measured. The results are shown in Table 2.
[0263] (Comparative Example 2) A nickel-cobalt-aluminum metal composite hydroxide was produced in the same manner as in Example 1, except that the taper angle of the wet classifier hydrocyclone was changed to 9° and the liquid flow rate was changed to 0.59 m / sec.
[0264] The obtained nickel-cobalt-aluminum metal composite hydroxide was subjected to particle size distribution measurement and composition analysis. The composition formula of the obtained nickel-cobalt-aluminum metal composite hydroxide is Ni 90.0 Co 7.0 Al 3.0 (OH) 2.1 It was.
[0265] A laminate cell was produced using the positive electrode active material for a lithium secondary battery obtained in the same manner as in Example 1, except that the nickel-cobalt-aluminum metal composite hydroxide was used, and the amount of battery swelling was measured. The results are shown in Table 2.
[0266] (Comparative Example 3) Slurry preparation process Water was placed in a 500 L cylindrical reaction vessel equipped with an agitator equipped with a 220φ propeller-type agitating blade and an overflow pipe, and then a 32 mass % sodium hydroxide solution was added until the pH reached 12.6 (measured when the solution temperature was 40°C), and the temperature was maintained at 60°C with a heater. Next, nitrogen gas was continuously blown into the reaction vessel at a flow rate of 5 L / min to make the atmosphere inside the reaction vessel an inert atmosphere.
[0267] A mixed raw material solution was prepared by mixing an aqueous nickel sulfate solution, an aqueous cobalt sulfate solution, and an aqueous manganese sulfate solution in an atomic ratio of nickel atoms, cobalt atoms, and manganese atoms of 88:8:4. The mixed raw material solution was continuously fed into a reactor at a constant rate. A 0.76 mol / L ammonium sulfate solution was used as a complexing agent, and the ammonia concentration was continuously fed into the reactor at a constant rate of 0.23 mol / L. Furthermore, 32% by mass of sodium hydroxide was intermittently added to maintain the pH of the solution in the reactor at 12.6 (measured when the solution temperature was 40°C).
[0268] The obtained nickel-cobalt-manganese metal composite hydroxide was washed and dehydrated, then dried at 105°C for 20 hours and sieved, and the particle size distribution and composition were analyzed. The composition formula of the obtained nickel-cobalt-manganese metal composite hydroxide was Ni 88.1 Co 9.0 Mn 2.9 (OH) 2.0 It was.
[0269] A laminate cell was produced using the positive electrode active material for a lithium secondary battery obtained in the same manner as in Example 1, except that the nickel-cobalt-manganese metal composite hydroxide was used, and the amount of battery swelling was measured. The results are shown in Table 2.
[0270] [Table 2]
[0271] As shown in Table 2, the battery of the example using the positive electrode containing the lithium secondary battery positive electrode active material produced using the precursor of this embodiment had a smaller amount of battery swelling than the comparative example. Therefore, it was confirmed that when the positive electrode active material produced using the precursor to which the present invention is applied is used, a battery with a longer life can be produced. [Explanation of symbols]
[0272] 1...separator, 2...positive electrode, 3...negative electrode, 4...electrode group, 5...battery can, 6...electrolyte, 7...top insulator, 8...sealing body, 10...lithium secondary battery, 21...positive electrode lead, 31...negative electrode lead, 100...laminated body, 110...positive electrode, 111...positive electrode active material layer, 112...positive electrode current collector, 113...external terminal, 120...negative electrode, 121...negative electrode electrolyte layer, 122...negative electrode current collector, 123...external terminal, 130...solid electrolyte layer, 200...exterior body, 200a...opening, 1000...all-solid-state lithium ion secondary battery
Claims
1. A method for producing a precursor for a positive electrode active material of a lithium secondary battery, the method comprising the steps of: (a) determining whether a particle diameter (μm) at which a cumulative volume ratio from the small particle side is 50% is 4.5 μm or more in a volume-based cumulative particle size distribution curve obtained by laser diffraction particle size distribution measurement; and (b) determining whether a particle diameter (μm) at which a cumulative volume ratio from the small particle side is 50% is 4.5 μm or more, the method comprising the steps of: The method includes a slurry preparation step of supplying a metal-containing aqueous solution containing at least nickel atoms and an alkaline aqueous solution to a reaction tank to obtain a hydroxide-containing slurry, and a classification step of classifying the hydroxide-containing slurry using a liquid cyclone classifier, wherein a taper angle θ of the tapered portion of the liquid cyclone classifier is 10° or more and 60° or less.
2. 2. The method for producing a precursor for a positive electrode active material of a lithium secondary battery according to claim 1, wherein the slurry flow rate of the liquid cyclone classifier is 0.6 m / sec or more and 1.5 m / sec or less.
3. 3. The method for producing a precursor for a positive electrode active material of a lithium secondary battery according to claim 1, further comprising a reflux step of returning the hydroxide-containing slurry classified by the liquid cyclone classifier to a reaction vessel.
4. 3. The method for producing a precursor for a positive electrode active material of a lithium secondary battery according to claim 1, which is a method for producing a precursor for a positive electrode active material of a lithium secondary battery represented by the following composition formula (A): Ni 1-x-y Coco x M y O z (OH) 2-α ・・・Composition formula (A) (In the composition formula (A), 0≦x≦0.45, 0≦y≦0.45, 0≦z≦3, and −0.5≦α≦2, and M is one or more metal elements selected from the group consisting of Mg, Ca, Sr, Ba, Zn, B, Al, Mn, Ga, Ti, Zr, Ge, Fe, Cu, Cr, V, W, Mo, Sc, Y, Nb, La, Ta, Tc, Ru, Rh, Pd, Ag, Cd, In, and Sn.)
5. 3. A method for producing a positive electrode active material for a lithium secondary battery, comprising the steps of mixing a precursor for a positive electrode active material for a lithium secondary battery obtained by the method for producing a precursor for a positive electrode active material for a lithium secondary battery according to claim 1 or 2 with a lithium compound, and calcining the resulting mixture.
Citation Information
Patent Citations
Preparation method of lithium ion battery positive electrode material and precursor thereof
CN108751265A
Positive electrode active material for nonaqueous electrolyte secondary batteries, and nonaqueous electrolyte secondary battery arranged by use thereof
JP2015043335A
Precursor for lithium secondary battery positive electrode active material, manufacturing method thereof, and manufacturing method of lithium composite metal compound
JP2020092070A